POZNAŃSKI „OKRĄGLAK” ORAZ WARSZAWSKI PAŁAC KULTURY – IDEOLOGICZNE PARADOKSY ARCHITEKTURY PO II WOJNIE ŚWIATOWEJ - GRZESZCZUK-BRENDEL, HANNA (Slavia Occidentalis, 2020)
A – department store commonly referred to as “Okrąglak” (“The Rotunda”) in Poznań and the Palace of Culture and Science in Warsaw, both completed in 1955, represent features of two opposing styles. This leads to further reflections on modernism and socialist realism as demonstrated by the – two buildings. The modern features of the tower of the Palace of Culture and Science have been outshined with the national form and communist contents clearly reflecting Poland’s subordination to the Soviet Union. References to the pattern, the Palace of the Soviets, defined the top-down accepted model of progress. The department store (“Okrąglak”), designed in 1948, was also meant to demonstrate modernity of commerce in a communist country. However, its form designed by Marek Leykam represents a more universal concept of progress free from any designations.